Pengaruh Komponen Wisata terhadap Kepuasan Wisatawan di Hutan Kota Bekasi - Yohana Magdalena, Yohana Magdalena; Ika Suryono Djunaid, Ika Suryono Djunaid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
There are several problems that affect the tourism component when tourists visit the Bekasi City Forest, when research is carried out with observations and questionnaires, there are several factors that affect tourist satisfaction in the City Forest, namely accessibility, attractions, amenities, ancillary and activities. This research was conducted with the aim of knowing the tourism component on tourist satisfaction whether it will have an effect. This research uses quantitative methods. The outer model test consists of validity test, reliability test, classical assumption test consisting of normality test, simple linear regression test, and hypothesis testing consisting of T test, correlation coefficient test, and determination coefficient test. The results showed that the independent variable had a positive effect on the dependent variable of 68,3% on Tourist Satisfaction while the remaining value of 31,7% was influenced by other factors not examined in this study.Suggestions from this study are to increase security, improve road access and facilities in the Bekasi City Forest. So that tourists can enjoy comfortably and safely.